Энергоэнтропийные принципы развития технической системы "гидрораспределитель" - Семёнова, Наталия Викторовна; Ратушный, Александр Валерьевич; Кулинич, Сергей Павлович (НТУ "ХПИ", 2016)
В статье рассмотрены основные закономерности развития технической системы "гидрораспределитель" на основе принципов энергоэнтропики. Проанализированы тенденции развития гидравлических распределителей с электрическим управлением. Показаны изменения в конструкциях распределителей, обусловленные необходимостью обеспечения лучших эксплуатационных характеристик и обоснованы направления дальнейшего их усовершенствования. Установлено, что улучшение технических характеристик, расширение возможностей связано с соответствием их конструкции второму и третьему принципам энергоэнтропики.

The article deals with the basic laws of development of the technical system ″hydraulic distribution valve″ based on the principles of energy entropy. It analyzes the design of various types of hydraulic valves. The focus of the article is the design, characteristics of hydraulic valves with electric control. The article deals with electrohydraulic valves of direct and indirect control. It analyzes the development trends of hydraulic valves with electric control. It describes the changes in the construction of distributors, which are determined by the need to ensure the best operating performance, and the directions for their further improvement. It is found that the improvement of technical characteristics and expanding the possibilities due to their design correspond to the second and third principles of energy entropy.
Energy entropy principles of the development of the technical system ″hydraulic distribution valve"
Keywords: развитие; золотник; электромагнит; техническая система; valve spindle; electromagnet